Ceramic circuit board and manufacturing method thereof
By incorporating Zr in the copper plates and employing a controlled brazing temperature profile, the ceramic circuit board achieves high electrical and thermal conductivity, overcoming the conductivity reduction issues associated with large grain sizes in copper plates.
Patent Information
- Application Number
- JP2021029383
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-10
- Filing Date
- 2021-02-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-02-26
AI Technical Summary
The electrical conductivity of copper plates bonded to ceramic substrates via brazing material is reduced due to excessive grain size, leading to potential deterioration in the electrical performance of ceramic circuit boards.
A ceramic circuit board design where the copper plate contains 0.03% to 0.15% by mass of Zr, with an average grain size of 100 μm or less, and a conductivity of 96% or more relative to the IACS standard, is bonded to a ceramic substrate using a specific temperature profile during the brazing process.
The approach results in a ceramic circuit board with high electrical conductivity and thermal conductivity of 375 W/m·K or more, effectively addressing the issue of conductivity reduction and maintaining the reliability of the circuit board.
Smart Images

Figure 0007658109000001 
Figure 0007658109000002 
Figure 0007658109000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ceramic circuit board used in a power module and a method for manufacturing the same. [Background technology]
[0002] A ceramic circuit board (hereinafter, sometimes simply referred to as a circuit board) is disclosed, for example, in Japanese Patent Application Laid-Open No. 2003-110222. The circuit board described in Japanese Patent Application Laid-Open No. 2003-110222 includes a copper plate bonded to at least one surface of a ceramic substrate via a brazing material. According to the disclosure in Japanese Patent Application Laid-Open No. 2003-110222, a copper plate is bonded to at least one surface of a ceramic substrate via a brazing material, a resist is applied to a predetermined portion of the surface of the copper plate, and unnecessary portions of the copper plate are etched to form a circuit portion, unnecessary brazing material and reaction products between the brazing material and the ceramic substrate are removed while maintaining the resist, and then the resist is peeled off to form a circuit pattern, thereby forming a circuit substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-110222 A Summary of the Invention [Problem to be solved by the invention]
[0004] For example, if the average crystal grain size of the copper plate constituting the circuit board is excessively large, there is a concern that the bonding with the ceramic substrate via the brazing material may be impaired. Therefore, when a copper plate formed with a relatively small average crystal grain size is bonded to one side of a ceramic substrate using a brazing material, the electrical conductivity of the copper plate constituting the circuit substrate decreases. There is a concern that the electrical performance of the circuit substrate may decrease due to the decrease in the electrical conductivity of the copper plate.
[0005] An object of the present invention is to provide a ceramic circuit board in which a copper plate having high electrical conductivity is bonded to one surface of a ceramic substrate via a brazing material layer, and a method for manufacturing the same. [Means for solving the problem]
[0006] In view of the above object, the inventors have conducted extensive research and found that the conductivity of the copper plate constituting the circuit board decreases due to the coarsening of crystal grains of the copper plate when it is bonded to a ceramic substrate via a brazing material. They also found that the decrease in the conductivity of the copper plate constituting the circuit board can be suppressed by devising a temperature profile when brazing the copper plate to the ceramic substrate, and thus arrived at the present invention.
[0007] The ceramic circuit board of the present invention is A ceramic circuit board comprising a copper plate bonded to one surface of a ceramic substrate via a brazing material layer, The copper plate is made of a copper alloy containing more than 0.03 mass% and not more than 0.15 mass% Zr, with the remainder being copper and unavoidable impurities, and has an average crystal grain size of 100 μm or less as measured by the intercepting method of the grain size test method for drawn copper products specified in JIS H0501:1986, and an electrical conductivity of 96% or more and less than 100% of the IACS standard.
[0008] In the above ceramic circuit board, the copper plate preferably has a thermal conductivity of 375 W / m·K or more.
[0009] In the above ceramic circuit board, the ceramic substrate may be a sintered silicon nitride substrate.
[0010] The method for producing a ceramic circuit board of the present invention comprises applying a brazing material to one surface of a ceramic substrate. layer Through copper plate but Joint was done A method for manufacturing a ceramic circuit board, comprising the steps of: The method includes a brazing material region forming step of forming a brazing material region on the one surface of the ceramic substrate, a placing step of placing a copper plate on the brazing material region to form a laminate, and a joining step of joining the ceramic substrate and the copper plate via the brazing material layer to form a joined body, wherein the copper plate is A copper alloy containing more than 0.03 mass% and not more than 0.15 mass% Zr, with the balance being copper and unavoidable impurities. the law of nature , The bonding step isTemperatures in the range of 770-880°C Hold it in The method includes a heating step of heating the material, and a cooling step of lowering the temperature to 350° C. over a period of 50 minutes or more after the heating step. nothing. Effect of the Invention
[0011] The present invention can provide a ceramic circuit board including a copper plate with high electrical conductivity and a method for manufacturing the same. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a front view showing a schematic diagram of a ceramic circuit board. [Diagram 2] FIG. 2 is a plan view of FIG. 1 seen from above. [Diagram 3] FIG. 2 is a first plan view illustrating a method for manufacturing the ceramic circuit board of FIG. [Figure 4] 1. FIG. 4 is a second plan view illustrating the method for manufacturing the ceramic circuit board of FIG. [Diagram 5] 1. FIG. 4 is a third plan view illustrating the method for manufacturing the ceramic circuit board of FIG. [Figure 6] 1. FIG. 4 is a fourth plan view illustrating the method for manufacturing the ceramic circuit board of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The ceramic circuit board of the present invention is, for example, the ceramic circuit board W shown in Fig. 1 and Fig. 2. The ceramic circuit board W basically comprises a ceramic substrate S, two brazing filler metal layers C1, C2 (hereinafter, sometimes referred to as the first brazing filler metal layer C1 and the second brazing filler metal layer C2) formed on the upper surface (one surface) of the ceramic substrate S with a gap G therebetween, and two copper plates M1, M2 (hereinafter, sometimes referred to as the first copper plate M1 and the second copper plate substrate M2) that function as circuit plates on which semiconductor elements or the like are mounted, respectively bonded to the upper surface side of the ceramic substrate S via the two brazing filler metal layers C1, C2. A plating layer of Ni, Au, or the like may be formed on the surfaces of the two copper plates M1, M2 as necessary. The ceramic circuit board W shown in Fig. 1 and Fig. 2 has a copper plate M3 that functions as a heat sink and is bonded to the lower surface (other surface) of the ceramic substrate S via the brazing filler metal layer C3. The number of copper plates is not limited to two, M1 and M2, and three or more copper plates may be provided on the upper surface side.
[0014] The ceramic substrate constituting the ceramic circuit board of the present invention is not particularly limited in type, and may be made of alumina, silicon carbide, or the like, but silicon nitride or aluminum nitride is preferred from the viewpoint of high thermal conductivity. The maximum diameter of the pores present on the surface of the ceramic substrate is preferably 15 μm. If the maximum diameter of the pores exceeds 15 μm, the strength of the ceramic substrate decreases, for example, deteriorating the reliability of the ceramic circuit board under thermal cycles. It is more preferred to use a silicon nitride sintered body, which is particularly excellent in mechanical strength such as strength and fracture toughness.
[0015] The silicon nitride sintered body can be produced, for example, by using a raw material powder containing 90 to 97% by mass of silicon nitride and 0.5 to 10% by mass of a sintering aid (containing a compound of Mg and at least one compound of Y and other rare earth elements). Specifically, the silicon nitride sintered body is produced by adding an appropriate amount of an organic binder, a plasticizer, a dispersant, and an organic solvent to the raw material powder, mixing them in a ball mill or the like to form a slurry, and forming the slurry into a thin plate shape by a doctor blade method or a calendar roll method to obtain a ceramic green sheet. The obtained ceramic green sheet can be obtained by punching or cutting into a desired shape and sintering at a temperature of 1700 to 1900°C. In this case, if the sintering aid exceeds 10% by mass, the characteristics of bonding the ceramic substrate and the copper plate may become insufficient. Also, if the sintering aid is less than 0.5% by mass, the sintering of the silicon nitride particles may become insufficient. In order to obtain high thermal conductivity and high strength, it is preferable to contain, as a sintering aid, magnesium (Mg) in an amount of 2 to 4 mass % calculated as magnesium oxide, and yttrium (Y) in an amount of 2 to 5 mass % calculated as yttrium oxide.
[0016] In the ceramic circuit board of the present invention, the number of copper plates bonded to one side of the ceramic substrate via the brazing material is not particularly limited. The copper plates constituting the ceramic circuit board of the present invention are made of a copper alloy containing more than 0.03 mass% to 0.15 mass% or less of Zr, with the remainder being copper and unavoidable impurities. The copper plates are preferred in terms of electrical resistance and ductility, high thermal conductivity (low thermal resistance), and low migration.
[0017] The method for manufacturing a ceramic circuit board of the present invention includes a bonding step of bonding a copper plate to one surface of a ceramic substrate via a brazing material, the bonding step including a heating step of heating the copper plate, which is made of a copper alloy containing more than 0.03 mass % and not more than 0.15 mass % Zr, with the remainder being copper and unavoidable impurities, at a temperature in the range of 770 to 880°C, and a cooling step of lowering the temperature to 350°C over a period of 50 minutes or more after the heating step.
[0018] Hereinafter, the method for manufacturing the ceramic circuit board of the present invention will be described with reference to the drawings as appropriate, taking the case of manufacturing the ceramic circuit board W shown in Figures 1 and 2 as an example. Here, the method for manufacturing the ceramic circuit board W can be divided into, for example, (a) a preparation step of preparing a ceramic substrate, a brazing material, and a copper plate, (b) a brazing material region forming step of applying a brazing material to the ceramic substrate, (c) a placement step of stacking the ceramic substrate, the brazing material, and the copper plate in this order, (d) a bonding step, (e) a circuit pattern forming step of etching the copper plate, (f) an unnecessary brazing material layer removing step, and (g) a cleaning step. The (d) bonding step includes the "heating step" and "cooling down step" in the method for manufacturing the ceramic circuit board of the present invention.
[0019] (a) Preparation process A ceramic substrate S, a brazing material (a paste containing brazing material powder and an organic binder), and a copper plate M are prepared.
[0020] (b) Brazing material area formation process 3, the brazing material is applied to the ceramic substrate S by a method such as screen printing to form brazing material regions c1 and c2 containing brazing material powder and an organic binder with a gap G. The brazing material powder may be a brazing material powder containing Ag, Cu, etc. in a predetermined composition, and various organic resins may be used as the organic binder.
[0021] (c) Placing process A copper plate M is placed on the side of the ceramic substrate S on which the brazing material is applied, and is fixed in place using a jig.
[0022] (d) Bonding process The bonding process includes a "heating process" and a "temperature-lowering process". A holding process may be added to the bonding process. As shown in FIG. 4, (i) a ceramic substrate S, (ii) brazing material regions c1, c2 formed on the ceramic substrate and containing a brazing material powder and an organic binder, and (iii) a copper plate M placed through the brazing material region are heated to bond the ceramic substrate S and the copper plate M through the brazing material layer, forming a bonded body. Heating for bonding is preferably performed in a vacuum or a reducing atmosphere. In order to remove organic components in the brazing material paste during the heating process, it is preferable to hold the temperature near the volatilization temperature of the organic binder (for example, near 400°C) once (holding process). Thereafter, the material is heated at a brazing temperature of 770 to 880°C (heating process (brazing process)). The heating process is preferably continued for 10 minutes or more. The brazing temperature is a temperature at which a brazing material layer can be appropriately formed, that is, a temperature equal to or higher than the melting point of the brazing material. The brazing temperature is usually the maximum temperature during the heating process. After the heating process, the temperature is lowered to 350°C over a period of 50 minutes or more (cooling down process).Then, the temperature is lowered from 350°C to room temperature.
[0023] In the holding step in the joining step, if the holding temperature for removing the organic binder is low, the organic binder components cannot volatilize, and there is a risk that organic binder residues will remain. Therefore, the holding temperature for removing the organic binder is preferably 300°C or higher. For example, in the case of an organic binder containing an acrylic resin, this holding temperature is preferably 360°C or higher. In order to prevent the active metal in the brazing material from being oxidized by oxygen contained in the resin in the organic binder, the holding temperature for removing the organic binder is set lower than the brazing temperature in the heating step (brazing step).
[0024] The brazing material used in the bonding step is preferably, for example, an Ag-Cu-based active brazing material, which is a eutectic composition of Ag and Cu as the main components and which has been added with active metals such as Ti, Zr, and Hf, and which can provide high strength and high sealing properties. Furthermore, from the viewpoint of the bonding strength between the ceramic substrate S and the copper plates M1 to M3, a ternary Ag-Cu-In-based active brazing material, in which In is added to the Ag-Cu-based active brazing material, is more preferable. The bonding between the ceramic substrate S and the copper plates is performed using a brazing material paste containing the brazing material powder and an organic binder, as described above. For example, an Ag-Cu-based active brazing material having a melting point of 770 to 880°C is used as the brazing material, and the brazing temperature is preferably set to 770 to 880°C. If the temperature is 770°C or higher, the brazing material is sufficiently melted, and the formation of voids is suppressed. More preferably, the temperature is set to 790°C or higher. If the temperature is 880°C or lower, the brazing material does not spread too much. More preferably, the brazing temperature is set to 830 to 870°C. The time to hold at the brazing temperature depends on the amount of samples put into the bonding furnace, but is preferably within 5 hours, more preferably within 2 hours, in consideration of normal productivity. The time to hold at the brazing temperature is appropriately adjusted and set according to the number of samples put in, or, for example, in the case of a vacuum atmosphere, according to the volume of the bonding furnace or the displacement of the vacuum pump. In order to bond the copper plate and the ceramics without voids, it is preferable to apply a load to fix them in the placing process and heat them in the bonding process.
[0025] When a general oxygen-free copper is used for the copper plate, there is a concern that the crystal grain size will grow to a size exceeding 300 μm when heated at the brazing temperature. In contrast, the copper plate using the copper alloy containing more than 0.03 mass% and 0.15 mass% or less of Zr of the present invention can suppress the average crystal grain size to 100 μm or less even when heated at the brazing temperature. Here, when the Zr content is 0.03 mass% or less, the average crystal grain size cannot be suppressed to 100 μm or less when heated at the brazing temperature. In addition, when the Zr content exceeds 0.15 mass%, the electrical conductivity decreases significantly, and there is a concern that it is not possible to ensure 96% or more of the IACS standard.
[0026] Furthermore, in the copper plate of the present invention, when heated to the brazing temperature, most of the Zr is dissolved in the copper matrix, and high electrical conductivity cannot be ensured in this state. Therefore, in order to ensure high electrical conductivity, the plate is slowly cooled from the brazing temperature to 350°C over a period of 50 minutes or more. This allows Zr to change from a state in which it is dissolved in the copper matrix in the temperature range from 550°C to 350°C to a state in which it forms a phase separate from the matrix and precipitates. By cooling slowly, sufficient time is ensured to pass through the above temperature range, so that the precipitation of Zr progresses and the copper matrix becomes highly purified, thereby obtaining high electrical conductivity. Note that if the cooling time from the brazing temperature to 350°C is shorter than 50 minutes, the precipitation of Zr becomes insufficient, and there is a concern that electrical conductivity of 96% or more cannot be ensured according to the IACS standard.
[0027] The content of unavoidable impurities in the copper plate is preferably suppressed to the same level as the content of impurities in oxygen-free copper, and more preferably to less than 0.04 mass%. The average crystal grain size of the copper plate is preferably 60 μm or less, more preferably 30 μm or less. It is more preferable that the thermal conductivity of the copper plate is 380 W / m·K or more. It is preferable that the average crystal grain size of the copper plate is G≦100 μm and the copper plate thickness T≧0.2 mm (T / G≧2.0). For example, when G=60 μm and T=0.3 mm, T / G=5.0, when G=60 μm and T=0.5 mm, T / G=8.3, and when G=60 μm and T=0.8 mm, T / G=13.3.
[0028] When an acrylic resin is used as the organic binder contained in the brazing paste, deposits resulting from the gasified acrylic resin tend to adhere to the ceramic substrate surface during the heating process. Therefore, when an acrylic resin is used as the organic binder, examples of suitable binders include polyacrylic esters and polymethacrylic esters. Methacrylic esters are preferably used.
[0029] (e) Circuit pattern formation process For the bonded body obtained in the bonding process, resist films R1, R2 are formed on the surface of the copper plate M in a pattern that follows the outer edge of the brazing material layer formed in the bonding process, as shown in FIG. 5, and the copper plate M is divided by etching to form circuit patterns M1, M2 as shown in FIG. 6.
[0030] (f) Unnecessary brazing material layer removal process After the circuit pattern forming step (e), an unnecessary brazing material layer removing step can be provided to remove unnecessary brazing material layers. The resist film is preferably formed in a pattern that follows the outer edge of the brazing material layer formed in the bonding step. The resist film formed in the circuit pattern forming step can be thin, having a thickness of 10 to 80 μm, preferably 30 to 70 μm. The resist film is desirably formed from an ultraviolet-curable resist agent.
[0031] For example, when a chemical solution containing hydrogen peroxide and acidic ammonium fluoride is used as the brazing material remover, an aqueous solution containing 10 to 40 mass% (2.9 to 8.8 mol / L) hydrogen peroxide and 1 to 8 mass% (0.7 to 2.1 mol / L) acidic ammonium fluoride can be used. If the hydrogen peroxide is less than 10 mass%, the ability to remove the brazing material is insufficient, and if it exceeds 40 mass%, the copper plate is excessively corroded, and the dimensional accuracy of the copper plate is deteriorated. If the acidic ammonium fluoride is less than 1 mass%, the ability to remove the reaction layer containing active metal generated at the bonding interface between the brazing material layer and the ceramic substrate is reduced, while if it exceeds 8 mass%, the crystal particles constituting the ceramic substrate are dissolved, and the electrical insulation and strength required for the ceramic substrate are reduced.
[0032] (g) Cleaning process In the cleaning step, the bonded body is immersed in a chemical to clean it. For example, if the oxygen in the atmosphere is not sufficiently reduced and the surface of the copper plate is oxidized in the heating step, this is not preferable because it may lead to a decrease in electrical conductivity and a decrease in solderability. Therefore, the bonded body is immersed in a chemical containing at least one selected from hydrogen peroxide, sulfuric acid, hydrochloric acid, and ammonium chloride to clean it, thereby removing the oxides on the surface of the copper plate. It is preferable to use sulfuric acid as the chemical.
[0033] After the above steps (e) to (g), deposits that reduce the insulation resistance between the copper sheets are removed or reduced.
[0034] As another step, after the (g) cleaning step, a (h) plating step may be included in which a plating layer of Ni, Au, Ag, etc. is formed on the surface of the copper plate. For example, when Ni plating is performed, a Ni plating layer having a thickness of about 5 μm can be formed on the surface of the copper plate by immersing the copper plate for 20 to 30 minutes in an electroless plating solution (85°C) containing nickel (Ni) as the main component and with a phosphorus (P) concentration adjusted to 8 mass%.
[0035] The present invention will now be described with reference to the following examples, without however being limited thereto.
[0036] (Example) The common parts of the examples will be explained as [(a) preparation process] to [(g) cleaning process], and then the copper plate and the joining process will be explained in Examples 1 to 4 and Reference Examples 1 to 5.
[0037] [(a) Preparation process] A copper plate, a brazing material, and a ceramic substrate are prepared. As the ceramic substrate S, a silicon nitride substrate containing 93 mass% of Si3N4, 4 mass% of Mg in terms of oxide, and 3 mass% of Y in terms of oxide in 100 mass parts of the total raw material powder (when shown on the paper surface shown in FIG. 2, the length and width are 30 mm and 40 mm, respectively, and the thickness is 0.32 mm) is used. As the brazing material, a brazing material paste is used, which is a mixture of 5.3 mass parts of polyacrylic acid ester as an organic binder, 19.1 mass parts of α-terpineol as an organic solvent, and 0.5 mass parts of polyoxyalkylene alkyl ether and alkylbenzene sulfonate as a dispersant, with 100 mass parts of brazing material powder adjusted to have a composition of 70.6 mass% Ag, 2.9 mass% In, 1.9 mass% Ti, the remainder being Cu and a trace amount of impurities.
[0038] 3 to 6, which are plan views showing the steps of the manufacturing method for the ceramic circuit board S. In the manufacturing process for the ceramic circuit board S described below, the steps for forming the copper plates M1 and M2, which are the circuit plates, and the copper plate M3, which is the heat sink plate, are basically the same, so only the copper plates M1 and M2 will be described in detail, and the copper plate M3 will be omitted.
[0039] [(b) Brazing material region formation process] As shown in Fig. 3, two brazing filler metal regions c1, c2, each having a thickness of 40 μm, are formed on the upper surface (one surface) of the ceramic substrate S by applying brazing filler metal paste by screen printing in a planar direction with a gap G therebetween. In the paper space shown in Fig. 3, the size of the first brazing filler metal region c1 is 27.6 mm and 11.6 mm in length and width, respectively, the size of the second brazing filler metal region c2 is 27.6 mm and 23.6 mm in length and width, respectively, and the distance between the brazing filler metal regions c1 and c2 in the gap G is 1.0 mm.
[0040] [(c) Placing process] After the brazing material region forming process, as shown in FIG. 4, a copper plate M having a thickness of 0.5 mm and a size sufficient to cover the brazing material regions c1, c2 is placed on the brazing material regions c1, c2, and the ceramic substrate S, the brazing material regions c1, c2 and the copper plate M are laminated and fixed using a jig.
[0041] [(d) Joining process] The copper plate M is inserted into a heating furnace and heated in a vacuum atmosphere to bond the ceramic substrate S and the copper plate M via the brazing layers C1 and C2 to form a bonded body. Taking into consideration the thermal expansion of the copper plate M during the bonding process, the copper plate M has a length and width of 29.5 mm and 39.5 mm, respectively, in the plane of FIG. 4, which is smaller than the size of the ceramic substrate S.
[0042] The joining process is performed using a temperature pattern that includes a holding step of holding the material at 400°C, which is the removal temperature of the acrylic resin, which is an organic binder, for 10 hours, a temperature increase step of heating the material at a constant temperature increase rate from the holding step, a heating step (brazing step) of holding the material at 770°C to 880°C, which is the melting temperature of the brazing material, for 1 hour, a temperature decrease step of lowering the temperature to 350°C over a period of 50 minutes or more after the heating step, and a step of lowering the temperature from 350°C to room temperature.
[0043] [(e) Circuit pattern formation process] After the bonding process, as shown in Fig. 5, two resist films R1 and R2 are formed in a desired pattern on the surface of the copper plate M constituting the bonded body, and then etching is performed to remove unnecessary parts of the copper plate M, and two copper plates M1 and M2 are formed as circuit patterns with a gap G in the planar direction as shown in Fig. 6. Specifically, a bonded body in which an ultraviolet-curable etching resist is applied to the surface of the copper plate M by screen printing in a pattern corresponding to the dimensions of the first copper plate M1 and the second copper plate M2 described below is immersed in an etching solution [ferric chloride (FeCl3) solution (46.5Be)] at a liquid temperature of 50°C to form the copper plates M1 and M2. In addition, in the paper surface shown in Fig. 6, the length and width of the first copper plate M1 are 28 mm and 12 mm, respectively, and the length and width of the second copper plate M2 are 28 mm and 24 mm, respectively.
[0044] [(f) Unnecessary brazing material layer removal process] As shown in FIG. 6, the resist film formed on the surfaces of the copper plates M1 and M2 is removed, and the unnecessary brazing material layer protruding from the outer edges of the copper plates M1 and M2 is removed with a brazing material remover containing 7.6 mol / L hydrogen peroxide and acidic ammonium fluoride at a liquid temperature of 40° C. for a treatment time of 40 minutes.
[0045] [(g) Cleaning process] The ceramic circuit board is washed by immersing it in sulfuric acid having a concentration of 1 mol / L and a temperature of 50° C. for 10 minutes, and then the washing liquid is removed and the board is dried to obtain the circuit board.
[0046] The average grain size of copper plate can be measured using the cutting method of the grain size test method for copper products specified in JIS H0501. The surface of the copper plate is polished to a mirror finish with polishing paper and alumina abrasive grains, and then the surface is etched with ammonia water to which hydrogen peroxide has been added to reveal the grain boundaries. The revealed crystalline structure is photographed using a microscope, and a line of known length is drawn on the photograph, and the number of grains completely cut by the line is counted, and the average of the cut lengths is taken as the average grain size.
[0047] The conductivity of a copper plate can be measured, for example, using a Sigma Test eddy current conductivity meter manufactured by Forster. An AC magnetic field is generated by a probe that is in contact with the surface of the copper plate, and the conductivity is measured by detecting the strength of the eddy currents generated in the copper plate by the change in the magnetic field with the probe. With the Sigma Test, the measured conductivity value can be displayed in both % units according to the IACS standard and MS / m units according to the SI system of units.
[0048] It is difficult to measure the thermal conductivity of only the copper plate when it is joined to the ceramic substrate. However, it is known that there is a proportional relationship between thermal conductivity and electrical conductivity, called the Wiedemann-Franz law. Therefore, the thermal conductivity of the copper plate can be calculated from the measured electrical conductivity using the following formula based on the Wiedemann-Franz law.
[0049] K=LTσ K: Thermal conductivity (W / m K) σ: Electrical conductivity (S / m) L: Corrected Lorentz number for copper at 20°C, 2.3×10 -8 W / S·K 2 T: Temperature (K)
[0050] The reasons for the Zr content of the copper plate specified in the present invention will be explained with reference to examples and reference examples. In Examples 1 to 4, in which the Zr content satisfies the range specified in the present invention, the copper plate has a small average crystal grain size of 100 μm or less, and is excellent in bondability to ceramic substrates. In addition, the copper plate has an electrical conductivity of 96% or more of the IACS standard, and a thermal conductivity of 375 W / m·K or more. In Examples 1 to 4, an arbitrary 120 μm wide area was observed, and it was smooth, with no recesses of 20 μm or more in width.
[0051] Example 1 For the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.04 mass% was used in [(d) Joining process]. In the brazing process, the ambient temperature was adjusted in a brazing device to a brazing temperature of 800°C, and the holding time was set to 1 h (heating process). After that, the ambient temperature was lowered from the brazing temperature to 350°C over 50 minutes (temperature lowering process). The average crystal grain size of the copper plate was measured for the fabricated circuit board, and was found to be 60 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and it was found to be smooth. In addition, the electrical conductivity of the copper plate was measured, and was found to be 98% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 383 W / m·K.
[0052] Example 2 In the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.07 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was 800°C, and the holding time was 1 h (heating process) as in Example 1. Thereafter, the atmospheric temperature was lowered from the brazing temperature to 350°C over 50 minutes (temperature lowering process) as in Example 1. The average crystal grain size of the copper plate was measured for the fabricated circuit board and found to be 30 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and found to be smooth. In addition, the electrical conductivity of the copper plate was measured and found to be 97% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 379 W / m·K.
[0053] Example 3 In the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.15 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was 800°C, and the holding time was 1 h, as in Example 1 (heating process). Thereafter, the atmospheric temperature was lowered from the brazing temperature to 350°C over 50 minutes, as in Example 1 (temperature lowering process). The average crystal grain size of the copper plate was measured for the fabricated circuit board, and was 15 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and it was smooth. In addition, the electrical conductivity of the copper plate was measured, and was 96% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 375 W / m·K.
[0054] Example 4 In the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.04 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was set to 880°C and the holding time was set to 1 h (heating process). Thereafter, as in Example 1, the atmospheric temperature was lowered from the brazing temperature to 350°C over 50 minutes (temperature lowering process). The average crystal grain size of the copper plate was measured for the fabricated circuit board and found to be 100 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing layer and found to be smooth. In addition, the electrical conductivity of the copper plate was measured and found to be 98% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 383 W / m·K.
[0055] In comparison with the above examples, in Reference Example 1, in which the Zr content is less than the range specified in the present invention, the average crystal grain size of the copper plate exceeds 100 μm, and the bondability of the ceramic substrate is reduced. In Reference Example 2, in which the Zr content is more than the range specified in the present invention, the electrical conductivity of the copper plate is less than 96% of the IACS standard, and the thermal conductivity is also less than 375 W / m K.
[0056] ·Reference example 1 In the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.03 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was 800°C, and the holding time was 1 h, as in Example 1 (heating process). Thereafter, the atmospheric temperature was lowered from the brazing temperature to 350°C over 50 minutes, as in Example 1 (temperature lowering process). The average crystal grain size of the copper plate was measured for the fabricated circuit board, and was found to be 110 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and one recess with a width of about 20 μm was found. In addition, the electrical conductivity of the copper plate was measured, and was 98% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 383 W / m·K.
[0057] ·Reference example 2 For the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.18 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was 800°C, and the holding time was 1 h (heating process) as in Example 1. Thereafter, the atmospheric temperature was lowered from the brazing temperature to 350°C over 50 minutes (temperature lowering process) as in Example 1. The average crystal grain size of the copper plate was measured for the fabricated circuit board and found to be 15 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and found to be smooth. In addition, the electrical conductivity of the copper plate was measured and found to be 95% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 371 W / m·K.
[0058] The reasons for the temperature range of the heating step and the cooling time of the cooling step in the bonding process specified in the present invention will be explained with examples and reference examples. In the above-mentioned Examples 1 to 4, the temperature of the heating step and the cooling time of the cooling step satisfy the ranges specified in the present invention, and the average crystal grain size of the copper plate in all cases is small, at 100 μm or less, and the bonding properties of the ceramic substrate are excellent. In addition, the electrical conductivity of the copper plate is 96% or more of the IACS standard, and the thermal conductivity is 375 W / m·K or more.
[0059] Reference Examples 3 and 4 are examples in which the temperature of the heating step is outside the range specified by the present invention. In Reference Example 3, where the temperature is less than 770°C, the brazing material is not melted sufficiently, so that the bonding strength of the ceramic substrate is reduced. In Reference Example 4, where the temperature exceeds 880°C, the brazing material spreads too much, so that the bonding strength of the ceramic substrate is reduced. In addition, if the temperature is too high, there is a risk that the average crystal grain size of the copper plate will exceed 100 μm.
[0060] Reference Example 5 is an example in which the cooling time in the temperature lowering step is shorter than the time specified in the present invention. In this case, the electrical conductivity of the copper plate is less than 96% of the IACS standard, and the thermal conductivity is also less than 375 W / m·K.
[0061] ·Reference example 3 For the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.04 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was set to 750°C and the holding time was set to 1 h (heating process). After that, the ambient temperature was lowered from the brazing temperature to 350°C over 50 minutes (cooling down process). The average crystal grain size of the copper plate was measured for the fabricated circuit board and found to be 30 μm. In addition, when an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, two recesses with a width of about 20 μm were found. In addition, the electrical conductivity of the copper plate was measured and found to be 98% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 383 W / m·K.
[0062] ·Reference example 4 For the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.04 mass% was used in [(d) Joining process]. The brazing process was performed at a brazing temperature of 900°C for 1 h (heating process). After that, the ambient temperature was lowered from the brazing temperature to 350°C over 50 minutes (cooling process). The average crystal grain size of the copper plate was measured for the fabricated circuit board and found to be 110 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing layer, and one recess with a width of about 20 μm was found. The electrical conductivity of the copper plate was measured and found to be 98% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 383 W / m·K.
[0063] ·Reference example 5 In the configuration described in [(a) Preparation process] to [(g) Cleaning process], a copper plate with a Zr content of 0.04 mass% was used in [(d) Joining process]. In the brazing process, the brazing temperature was 800°C, and the holding time was 1 h, as in Example 1 (heating process). After that, the atmospheric temperature was lowered from the brazing temperature to 350°C over 30 minutes (temperature lowering process). The average crystal grain size of the copper plate was measured for the fabricated circuit board, and was 60 μm. In addition, an arbitrary 120 μm wide area was observed at the interface between the copper plate and the brazing material layer, and it was smooth. In addition, the electrical conductivity of the copper plate was measured, and was 95% of the IACS standard. The thermal conductivity calculated from the measured electrical conductivity was 371 W / m·K. [Explanation of symbols]
[0064] A,B: Spherical electrode, C1, C2, C3: brazing material layer, c1, c2: brazing material area, G: gap, M1,M2,M3: Metal substrate, M: Metal substrate, R1, R2: resist film, S: ceramic substrate, W: Ceramic circuit board
Claims
1. A ceramic circuit board comprising a copper plate bonded to one surface of a ceramic substrate via a brazing material layer, The copper plate is made of a copper alloy containing more than 0.03 mass% and not more than 0.15 mass% Zr, with the remainder being copper and unavoidable impurities, and has an average crystal grain size of 100 μm or less as measured by a cutting method in the grain size test method for drawn copper products specified in JIS H0501:1986, and an electrical conductivity of 96% or more and less than 100% of the IACS standard.
2. 2. The ceramic circuit board according to claim 1, wherein the copper plate has a thermal conductivity of 375 W / m·K or more.
3. 3. The ceramic circuit board according to claim 1, wherein the ceramic substrate is a sintered silicon nitride substrate.
4. A method for manufacturing a ceramic circuit board in which a copper plate is bonded to one surface of a ceramic substrate via a brazing material layer, comprising the steps of: a brazing material region forming step of forming a brazing material region on the one surface of the ceramic substrate; a step of placing the copper plate on the brazing material region to form a laminate; a joining step of joining the ceramic substrate and the copper plate via the brazing material layer to form a joined body, The copper plate is made of a copper alloy containing more than 0.03 mass% and not more than 0.15 mass% Zr, with the remainder being copper and unavoidable impurities; The bonding step includes a heating step of heating the laminated body while maintaining the temperature within a range of 770 to 880°C, and a cooling step of lowering the temperature to 350°C over a period of 50 minutes or more after the heating step.
Citation Information
Patent Citations
Method of manufacturing metal-ceramic joined circuit board
JP2003110222A
Metal / ceramic bonding substrate
JP2011199315A
Copper alloy sheet material and manufacturing method thereof
JP2012046810A
Copper alloy sheet and manufacturing method of copper alloy sheet
JP2016216793A
Copper alloy sheet for heat radiation component and heat radiation component
JP2018059132A